Training in surgery of the temporomandibular joint: the UK trainers' perspective. Issue 1 (January 2017) - Elledge, Ross; Green, Jason; Attard, Alan
Abstract: Surgery of the temporomandibular joint (TMJ) is increasingly recognised as a subspecialist area of interest within our specialty and many procedures such as arthroscopy, arthroplasty, and replacement of the TMJ are becoming increasingly centralised and restricted to certain regions. We previously made a national survey of trainees and have sought to augment this with a survey of trainers to find out the nature of practice and patterns of referral nationally. We have also examined the consultants' expectations of competent final-year trainees. To do this we made an electronic survey of Fellows of the British Association of Oral and Maxillofacial Surgeons (BAOMS) and received 82 responses (26%). Many just provided simple treatments within their clinical practice, only 16 did arthroscopy, and 14 alloplastic joint replacements. From those who answered the question, only 10 would allow a competent final-year trainee to do an alloplastic joint replacement under supervision. Referrals for TMJ subspecialist care were predominantly made to the West Midlands, East Midlands, and North West, with 24 respondents stating they would either refer open TMJ surgery centrally within or outside the region. Centralisation of services means that training opportunities in surgery of the TMJ are reduced, and restricted to only a few regions. Other models of training may need to be introduced such as simulation, "taster" sessions, and brief clinical attachments. For the budding subspecialist, however, a dedicated Fellowship may become essential to ensure adequate exposure before starting independent consultant practice.